2014
DOI: 10.1038/bjc.2014.610
|View full text |Cite
|
Sign up to set email alerts
|

Imaging tumour hypoxia with positron emission tomography

Abstract: Hypoxia, a hallmark of most solid tumours, is a negative prognostic factor due to its association with an aggressive tumour phenotype and therapeutic resistance. Given its prominent role in oncology, accurate detection of hypoxia is important, as it impacts on prognosis and could influence treatment planning. A variety of approaches have been explored over the years for detecting and monitoring changes in hypoxia in tumours, including biological markers and noninvasive imaging techniques. Positron emission tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
293
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(298 citation statements)
references
References 85 publications
(124 reference statements)
3
293
0
2
Order By: Relevance
“…The most widely used surrogate metric of tumor hypoxia in 18 F-FMISO PET is its TBR derived from a single late-time-point image. Investigators have reported times from 2-4 h after 18 F-FMISO administration (12,27,28). An image voxel is considered to be hypoxic if TBR exceeds a predetermined value, usually 1.2-1.4 (18,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most widely used surrogate metric of tumor hypoxia in 18 F-FMISO PET is its TBR derived from a single late-time-point image. Investigators have reported times from 2-4 h after 18 F-FMISO administration (12,27,28). An image voxel is considered to be hypoxic if TBR exceeds a predetermined value, usually 1.2-1.4 (18,27).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have reported times from 2-4 h after 18 F-FMISO administration (12,27,28). An image voxel is considered to be hypoxic if TBR exceeds a predetermined value, usually 1.2-1.4 (18,27). This approach, although simple to implement, may misidentify hypoxic voxels, a consequence of the slow 18 F-FMISO clearance from regions of high tumor perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative tracers which act as surrogates for hypoxia include fluorine-18 fluoroazomycin-arabinofuranoside and copper-64 diacetyl-bis(N4-methylthiosemicarbazone). Both tracers have more favourable pharmacokinetics than fluoromisonidazole and hold promise for further research (an overview can be seen in the study of Feling et al 2015 79 ). Cellular mechanisms involved in tumour response to treatment include a reduction in cell proliferation, which can be assessed using fluorothymidine PET-CT and an increase in apoptosis, which could be evaluated using a specialized tracer such as fluorine-18 2-(5-fluoro-pentyl)-2-methyl-malonic acid, as a surrogate biomarker.…”
Section: Lung Carcinomamentioning
confidence: 99%
“…However, the longterm effectiveness of endocrine therapy is limited by the development of endocrine resistance, which is strongly associated with hypoxia in the tumor microenvironment [6]. A noninvasive technology for quantifying tumor hypoxia is 18 F-fluoromisonidazole (FMISO) positron emission tomography/computed tomography (PET/CT) imaging [7]. Investigators have reported FMISO uptake as a robust measure of intracellular hypoxia, and reduced hypoxic activity after endocrine therapy has been identified as a good predictive marker of clinical response in patients with HR-positive metastatic breast cancer [8].…”
Section: Introductionmentioning
confidence: 99%